Implementation of the Additive Ratio Assessment (ARAS) Method for Evaluating Company Leadership Performance - Devi Sartika; Venny Novita Sari; Ila Yati Beti (International Journal of Artificial Intelligence Research, 2023)
Evaluating the performance of company leaders is an important process in determining leadership effectiveness and organizational success. Performance assessments that rely on subjective judgments often lead to less accurate decision-making results. Therefore, a systematic and objective decision-making method is required. One method that can be used is the Additive Ratio Assessment (ARAS) method. ARAS is a multi-criteria decision-making method used to determine the best alternative based on the utility value obtained from each evaluation criterion. This study aims to implement the ARAS method in a decision support system to evaluate the performance of company leaders. The research process involves several stages, including determining evaluation criteria, assigning weights to the criteria, normalizing the decision matrix, calculating optimal values, and determining utility values. The criteria used in this study include leadership, decision-making ability, communication, responsibility, and organizational performance. The results of the study indicate that the ARAS method can provide objective and systematic evaluation results in determining the best leadership performance. With the implementation of a decision support system based on the ARAS method, companies can obtain more accurate evaluation results that can be used as a basis for decision-making in leadership development and improving the quality of company management